Cardiopulmonary determinants of reduced exercise tolerance in Fabry disease - De Marco, Oriana; Gambardella, Jessica; Bianco, Antonio; Fiordelisi, Antonella; Cerasuolo, Federica Andrea; Buonaiuto, Antonietta; Avvisato, Roberta; Capuano, Ivana; Amicone, Maria; Di Risi, Teodolinda; Riccio, Eleonora; Spinelli, Letizia; et al. (Frontiers in Cardiovascular Medicine, 2024)
Fabry disease (FD), also known as Anderson-Fabry disease, is a hereditary disorder of glycosphingolipid metabolism, caused by a deficiency of the lysosomal alpha-galactosidase A enzyme. This causes a progressive accumulation of glycosphingolipids in tissues and organs which represents the main pathogenetic mechanism of FD. The disease is progressive and multisystemic and is characterized by early symptoms and late complications (renal, cardiac and neurological dysfunction). Fatigue and exercise intolerance are early common symptoms in FD patients but the specific causes are still to be defined. In this narrative review, we deal with the contribution of cardiac and pulmonary dysfunctions in determining fatigue and exercise intolerance in FD patients.